The investment in job training: Why are SMEs lagging so much behind? - Rita K. Almeida; Reyes Aterido (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the link between firm size and the investment in job training by employers. Using a large firm level data set across 99 developing countries, we show that a strong and positive correlation in the investment in job training and firm size is a robust statistical finding both within and across countries with very different institutions and level of development. However, our findings do not support the view that this difference is mostly driven by market imperfections disproportionally affecting SMEs. Rather, our evidence is supportive of SMEs having a smaller expected return from the investment in job training than larger firms. Therefore, our findings call for caution when designing pro-SME policies fostering the investment in on the job training.
Keywords: J24; D24; 330; On-the-job training; firm size; firm level data; developing countries; Berufsbegleitende Ausbildung; Bildungsinvestition; Betriebsgröße; Klein- und Mittelunternehmen; Welt